GENDER,GROWTH, AND EARNINGS QUALITY:POTRET LAPORAN KEUANGAN SEKTOR KESEHATAN 2021-2024 - Emiliana Eva; Mirna Dyah Praptitorini (Worksheet : Jurnal Akuntansi, 2026)
This study aims to analyze the effect of earning growth, the reputation on public acconting firms(PAFs),firm size,and female CEOs on earnings quality. Earnings quality is an important indicator in assessing the reliability of earning information that reflects a company’s actual economic condition. This study is based on agency theory,which explains the potential conflict of interest between management and shareholders,thereby emphasizing the need of effective monitoring mechanisms to improve earnings quaity. The population of this study consists of healthcare sector companies lited on the indonesia stok exchange (IDX) during the 2021-2024 period. The sampling technique used is purposive sampling,resulting in asample of companies that meet the research criteria. The data used are secondary data obtained from companies’ financial statements and annual reports. Multiple linear regression analysis is employed as the data analysis method. Earnings quality ia measured using the ratio of operating cash flow to net reputation of PAFs and CEOs are measured using dummy variables, and firm size is measured using the natural logarithm of total asset. From the research results, it can be concluded that profit growth, KAP reputation, company size, and female CEOs have a negative and significant effect on profit quality.